Immune deployment increases larval vulnerability to predators and inhibits adult life‐history traits in a dragonfly. (4th July 2018) - Moore, Michael P.; Lis, Cassandra; Martin, Ryan A.
Abstract: While deploying immune defences early in ontogeny can trade‐off with the production and maintenance of other important traits across the entire life cycle, it remains largely unexplored how features of the environment shape the magnitude or presence of these lifetime costs. Greater predation risk during the juvenile stage may particularly influence such costs by (1) magnifying the survival costs that arise from any handicap of juvenile avoidance traits and/or (2) intensifying allocation trade‐offs with important adult traits. Here, we tested for predator‐dependent costs of immune deployment within and across life stages using the dragonfly, Pachydiplax longipennis . We first examined how larval immune deployment affected two traits associated with larval vulnerability to predators: escape distance and foraging under predation risk. Larvae that were induced to mount an immune response had shorter escape distances but lower foraging activity in the presence of predator cues. We also induced immune responses in larvae and reared them through emergence in mesocosms that differed in the presence of large predatory dragonfly larvae (Aeshnidae spp.). Immune‐challenged larvae had later emergence overall and lower survival in pools with predators. Immune‐challenged males were also smaller at emergence and developed less sexually selected melanin wing coloration, but these effects were independent of predator treatment. Overall, these results highlight how mounting an immune defence early in ontogeny can have substantial ecological and physiological costs that manifest both within and across life stages.